SWEET CORN IN CONDITION OF AMUR REGION - O. A. Kositsyna; V. F. Kirsanova (Овощи России, 2015)
The results of evaluation of the collection of sweet corn hybrids Bonus, Spirit, NOA, and Trophy for for earliness and yield are presented. The hybrids NOA and Bonuses are recommended for growing of sweet corn in the agro-climatic conditions of southern agricultural zone of the Amur Region.